CHILDFREE ACCORDING TO THE VIEW OF THE COMMUNITY OF MEDAN DISTRICT JOHOR MEDAN CITY - ABU BAKAR (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2023)
Some married couples decide to limit their offspring with clear reasons and are justified by the Shari'a, while others consider that having many children is a blessing for which one should be grateful. All of that is because everyone must have different perspectives, reasons and also different experiences in living a household life. Unlike the case with a handful of married couples who think that happiness in the household is not only obtained from the birth of a child. And marriage does not have to have children or offspring. In Indonesia, for example, we know the name Veronica Wilson, who decided not to have children. Likewise with Victoria Tunggono who decided to live a family life without having children who are popularly known as "Childfree". However, not a few among the Indonesian people questioned their decision and what was the reason behind the decision. This study aims to determine the public's view of childfree in Medan Johor District, Medan City. This research uses a qualitative descriptive method. Data were obtained through direct field observation, interviews and documentation. The results of the study concluded that the Medan Johor District Community stated that childfree is not a principle in married life. Because it is contrary to the Sunnah of the Prophet SAW. This can be seen from the statements of sources or informants that the author met when making direct observations in the field by proposing the child free theme.